1994
DOI: 10.1111/j.1469-8137.1994.tb03002.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness constraints on flower number, seed number and seed size in the dimorphic species Primula farinosa L. and Armeria maritima (Miller) Willd.

Abstract: SUMMARYUsing two dimorphic species with diallelic incompatibility. Primula farinosa \^. and Armeria maritima (Miller) Willd., we tested the hypothesis that an association of seedling performance with seed size, and an inverse association of seed size with seed numher, tnight, contrary to most fitness models, select for plants which set relatively few seeds.In P. farinosa we discovered positive relationships between seed number per eapsule and capsule nutiiber per inflorescence. As capsules are formed in most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 60 publications
5
34
0
1
Order By: Relevance
“…In the authors' opinion such dependence may indirectly influence the reproductive success of this species, as inflorescences with few flowers set the fewest seeds per capsule. In the present study no such correlation was found, but we agree with Baker et al (1994) on the fact that the positive correlation between the increase of number of seeds per fruit and number of fruits per inflorescence may result in competition for limited maternal resources among seeds, and reduction in seed size may be a consequence of such a relationship. Furthermore, according to Boyd et al (1990), In vitro derived specimens who examined the population ecology of heterostyle and homostyle Primula vulgaris in field populations, seeds compete for limited maternal resources, which results in a trade-off between seed size and seed number.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the authors' opinion such dependence may indirectly influence the reproductive success of this species, as inflorescences with few flowers set the fewest seeds per capsule. In the present study no such correlation was found, but we agree with Baker et al (1994) on the fact that the positive correlation between the increase of number of seeds per fruit and number of fruits per inflorescence may result in competition for limited maternal resources among seeds, and reduction in seed size may be a consequence of such a relationship. Furthermore, according to Boyd et al (1990), In vitro derived specimens who examined the population ecology of heterostyle and homostyle Primula vulgaris in field populations, seeds compete for limited maternal resources, which results in a trade-off between seed size and seed number.…”
Section: Discussionsupporting
confidence: 89%
“…In turn, results from long-term observations in natural Primula veris populations showed much lower fruiting intensity, which ranged from 9.0% to 52.3%, depending on the population (Morozowska and Urbański, 2000). Fruiting efficiency and seed set are important parameters characterizing plant fecundity, which is an essential component of fitness (Baker et al, 1994). The very high fruiting efficiency observed in the present study suggests strong reproductive potential of cultivated cowslip plants either regenerated vegetatively from tissue cultures or propagated generatively from seeds.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In general, it is accepted that, relative to large seeds, small seeds usually have reduced emergence (Zimmerman & Weis, 1983 ;Weller, 1985 ;Winn, 1988 ;Tripathi & Khan, 1990 ;Hendrix & Trapp, 1992 ;Rice et al, 1993 ;Prinzie & Chmielewski, 1994), higher mortality (Schaal, 1980 ;Tripathi & Khan, 1990 ;Bonfil, 1998) and lower seedling growth (Wulff, 1986a ;Hendrix et al, 1991 ;Dawson & Ehleringer, 1991 ;Baker et al, 1994 ;Moegenburg, 1996 ;Weiner et al, 1997 ;Vaughton & Ramsey, 1998 ;Bonfil 1998). However, other studies show no relationship between seed size and seedling performance in some species, as described by Cipollini & Stiles (1991), Rice et al (1993) and Vaughton & Ramsey (1998) for seed germination ; Hendrix & Trapp (1992) for seedling survival ; Dolan (1984) and Marshall (1986) for seedling growth.…”
Section: mentioning
confidence: 99%